Glycogen Synthase Kinase 3β Inhibitor (2'Z,3'E)-6-Bromo-indirubin-3'-Oxime Enhances Drug Resistance to 5-Fluorouracil Chemotherapy in Colon Cancer Cells - Liu, Kun-ping; Luo, Feng; Xie, Si-ming; Tang, Li-juan; Chen, Mei-xiang; Wu, Xue-fang; Zhong, Xue-yun; Zhao, Tong (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: To explore the effects and mechanism of glycogen synthase kinase 3β (GSK-3β) inhibitor (2'Z,3'E)-6-bromo-indirubin-3'-oxime (BIO) on drug resistance in colon cancer cells. Methods: The colon cancer SW480 and SW620 cells were treated with BIO, 5-fluorouracil (5-FU) and BIO/5-FU, separately. Cell cycle distribution, apoptosis level and efflux ability of rhodamine 123 (Rh123) were detected by flow cytometry. The protein expressions of P-glycoprotein (P-gp), multidrug resistance protein 2 (MRP2), thymidylate synthase (TS), β-catenin, E2F-1 and Bcl-2 were detected by Western blot. β-catenin and P-gp were stained with double immunofluorescence and observed under a confocal microscope. Results: BIO up-regulated β-catenin, P-gp, MRP2 and TS, enhanced the efflux ability of Rh123, decreased Bcl-2 protein and gave the opposite effect to E2F-1 protein in SW480 and SW620 cells. Furthermore, BIO significantly inhibited cell apoptosis, increased S and G2/M phase cells, and reduced the cell apoptosis induced by 5-FU in SW480 cells, whereas the effects were slight or not obvious in SW620 cells. Conclusion: GSK-3β was involved in drug resistance regulation, and activation of β-catenin and inhibition of E2F-1 may be the most responsible for the enhancement of 5-FU chemotherapy resistance induced by GSK-3β inhibitor BIO in colon cancer.